Product Delivery Distribution Route Design at UD. XYZ Use the Saving Matrix Method to Minimize Distribution Costs - Asyifa Freda Salsa Billa; Nova Indah Saragih; Prafajar Suksessanno Muttaqin (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
One of the problems that frequently happen in distribution management is the Vehicle Routing Problem (VRP). VRP aims to create an optimal route, which has a minimum total distance to meet consumer demand. This problem is being experienced by UD. XYZ which causes cost overruns. The purpose of this study is to design product distribution routes to minimize distribution costs at UD. XYZ. The method used is a saving matrix with a dynamic program approach, nearest neighbor, and nearest insertion. Furthermore, the analysis of the sensitivity of the load and fuel is carried out. The saving matrix method with a dynamic program approach is able to reduce the distance traveled per week from 184.44 km to 136.65 km. In addition, the dynamic approach is also able to reduce distribution costs by 15.16% or Rp. 36,559.35 per week with distribution costs for the existing condition of Rp. 241.096.60 to Rp. 204.537.25. Salah satu permasalahan yang sering dialami dalam manajemen distribusi adalah Vehicle Routing Problem (VRP). VRP bertujuan untuk membuat suatu rute yang optimal, yaitu memiliki total jarak minimum dalam memenuhi permintaan konsumen. Permasalahan ini sedang dialami oleh UD. XYZ yang menyebabkan pembengkakan biaya. Tujuan dari penelitian ini adalah merancang rute distribusi produk untuk meminimasi biaya distribusi pada UD. XYZ. Metode yang digunakan saving matrix dengan pendekatan program dinamis, nearest neighbor, dan nearest insertion. Selanjutnya dilakukan analisis sensitifitas muatan dan bahan bakar. Metode saving matrix dengan pendekatan program dinamis mampu memperkecil jarak tempuh per minggu yang semula 184,44 km menjadi 136,65 km. Selain itu pendekatan dinamis juga mampu menurunkan biaya distribusi sebesar 15,16% atau Rp36.559,35 per minggu dengan biaya distribusi kondisi saat ini Rp241.096,60 menjadi Rp204.537,25.